2011
DOI: 10.1371/journal.pone.0018155
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Parameters of Speciation Models Based on Refined Summaries of the Joint Site-Frequency Spectrum

Abstract: Understanding the processes and conditions under which populations diverge to give rise to distinct species is a central question in evolutionary biology. Since recently diverged populations have high levels of shared polymorphisms, it is challenging to distinguish between recent divergence with no (or very low) inter-population gene flow and older splitting events with subsequent gene flow. Recently published methods to infer speciation parameters under the isolation-migration framework are based on summarizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…However, in our case, these more sophisticated models have the property of having divergence time and specific migration rates as free parameters for several pairs of populations. A recent simulation study showed that the joint estimation of these two parameters in an ABC framework does not yield satisfying results (Tellier et al 2011). Indeed, it is not clear at the present time which summarization of the raw data set would allow for an accurate joint estimation of divergence times and migration rates within an ABC framework.…”
Section: Discussionmentioning
confidence: 92%
“…However, in our case, these more sophisticated models have the property of having divergence time and specific migration rates as free parameters for several pairs of populations. A recent simulation study showed that the joint estimation of these two parameters in an ABC framework does not yield satisfying results (Tellier et al 2011). Indeed, it is not clear at the present time which summarization of the raw data set would allow for an accurate joint estimation of divergence times and migration rates within an ABC framework.…”
Section: Discussionmentioning
confidence: 92%
“…A simulation study to compare a variant of Jaatha with MIMAR (Becquet & Przeworski 2007) and PopABC (Lopes et al. 2009) has been performed by Tellier et al. (2011).…”
Section: Methods and Modelsmentioning
confidence: 99%
“…Li & Stephan (2006) showed that it is worthwhile to use more information from the JSFS than these four summary statistics for inference of demographic histories using population genetic data. Other JSFS‐based sets of summary statistics are examined by Tellier et al. (2011), with the main conclusion that especially further division of the shared polymorphisms results in better estimations of divergence times and migration rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no sufficient summary statistics at hand, but for the IM model the joint site frequency spectrum (JSFS) between the two populations was reported to be a particularly informative summary statistic (Tellier et al, 2011). However, for N samples in each of the two demes, the JSFS has (N + 1) 2 − 2 entries, so even for small datasets it is very high-dimensional.…”
Section: The Evolutionary History Of Bornean and Sumatran Orang-utansmentioning
confidence: 99%